SERANGGA PARASITOID PADA KUPU TROIDES HELENA DAN PAPILIO ARISTOLOCIA - Rohmatullah, Arif; Atmowidi, Bambang Suryobroto Tri (saintis, 2009)
This study aimed to study the diversity of the pupal parasitoid T. helena and P. aristolochia in captivity butterfly Cicurug, Sukabumi. From the research results can be seen that there are specific relationships between parasitoids and their hosts. B. lasus and Xanthopimpla sp. (Hymenoptera) were found to pupal parasite P. aristolochia and solitary. While Megaselia sp. (Dipterans) found the parasite to T. helena and are gregarius. Pupae which had the parasite by a solitary parasitoid pupae were more common than the parasite by the parasitoid was gregarius.